An exploration of how positive emotions are expressed by older people and nurse assistants in homecare visits. Issue 11 (November 2017) - Heyn, Lena; Ellington, Lee; Eide, Hilde
Abstract: Objective: We don´t know how positive emotions are being expressed by patients and health care providers in consultations. The aim of this study is to identify positive emotions expressed by older people and nurse assistants to discuss the function of these in the visits. Method: This paper presents secondary analysis of consultations in the COMHOME project. In this pilot study, six transcribed consultations between nurse assistants and older people in home health care were analysed using a coding system for positive emotions with seven categories capturing both content and emotional intensity of positive affect. Results: We found 114 expressions of positive emotions, 63% from nurse assistants and 37% from patients. Patients mostly expressed gratitude, indicating that patients are grateful for being helped. Nurse assistants mostly expressed Praise or Support, indicating that they gave their patients positive affirmation. Conclusion: The praise and support given by nurse assistants to older people in home health care seemed effective in fostering relationships and maintaining patient resilience. Thus, we claim that emotional talk in communication also should include positive emotions. Practice Implication: Teaching health care providers about the importance of expressions of positive emotions should be integrated in communication skills training.